Efek Konsumsi Minuman Beralkohol terhadap Kadar Kreatinin - Dwi Purbayanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Long-term and excessive alcohol consumption is a risk factor for chronic diseases such as impaired kidney function. Acute and chronic alcohol consumption can increase blood pressure which is a risk factor for kidney damage. Oxidative stress play a role in the kidney damage that induced by ethanol. In this study aims to the description of creatinine levels in moderate and heavy alcohol drinkers in Jalan Mendawai Kota Palangka Raya. This study used the descriptive method to describe the effect of consuming alcohol on kidney function using creatinine level parameters. Total sample used is 20 people with snowballs Sampling technique. The inclusion criteria such as male, age over 20 years old, consumed alcohol more than 5 years, consumed alcohol every day. Creatinine examination was done by Jaffe Reaction method using Photometer 5010 V5 +. The results showed that 15 people (75%) had high creatinine levels and 5 people (25%) had normal creatinine levels.